2021
DOI: 10.21203/rs.3.rs-309630/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Risk Factors Analysis of Pulmonary Cement Embolism during Percutaneous Vertebroplasty or Kyphoplasty for Osteoporotic Vertebral Compression Fracture.

Abstract: Objective: The purpose of this research is to evaluate the risk factors and incidence of PCE during PKP or PVP for osteoporotic vertebral compression fracture (OVCF) based on postoperative computed tomography (CT).Methods: A total of 2344 patients who underwent PVP or PKP due to OVCF in our spine centre were analyzed retrospectively. According to the detection of postoperative pulmonary CT, the patients were divided into two groups: pulmonary cement embolism group (PCE group) and non pulmonary cement embolism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…Bone cement infusion in multiple segments has a signi cant impact on the biomechanics and load transfer of the entire spine. Among the bone cement leaks that lead to refractures, intervertebral disc leakage is the most common [6,13]. Sun [26] showed that if there is no leakage, the refracture is 7%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bone cement infusion in multiple segments has a signi cant impact on the biomechanics and load transfer of the entire spine. Among the bone cement leaks that lead to refractures, intervertebral disc leakage is the most common [6,13]. Sun [26] showed that if there is no leakage, the refracture is 7%.…”
Section: Discussionmentioning
confidence: 99%
“…However, statistics show that the rate of new vertebral compression fractures in patients after PKP was approximately 8.7%-18.4% [3][4][5][6], which makes postoperative refracture an important issue for clinicians. Previous retrospective studies have reported several possible risk factors for refracture, including associations between age, body mass index (BMI), clinical complication rate, bone mineral density (BMD), number of initial surgical segments, and surgical puncture method [3,[6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%